Sistematización de las intervenciones de enfermería en el parto humanizado: una revisión de la literatura científica - López López, Tatiana Micaela (2025)
Humanized labor empowers women to make conscious decisions about their bodies and the birthing process. Therefore, this research document aimed to systematize the nursing interventions used in humanized labor. The research methodology was systematic and bibliographic, starting with a review of sources in databases. The search was conducted in major health-related databases, obtaining a total of 36 articles. The main results determined that, in Ecuador, free positioning during the birthing process is being promoted in various health establishments. Additionally, for the implementation of humanized care in the nursing field, the importance of continuous updating and teamwork collaboration is emphasized. The relevance of a humanized approach to childbirth is highlighted, which is defined as a safe, natural, and participatory process that guarantees the woman’s right to be heard and to make informed decisions. It is emphasized that nursing staff must possess technical-scientific knowledge of the procedure to meet the needs of the pregnant woman. Finally, the research concluded that the humanized labor approach allows for freedom of positioning and minimizes unnecessary medical interventions. Furthermore, humanized care in childbirth aims to respect women’s rights and choices, providing comprehensive and person-centered care.